PENGARUH TUTOR SEBAYA DALAM PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS FISIKA SISWA SMA - Evi Durotun Nasihah; Supeno Supeno; Albertus Djoko Lesmono (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The application of problem based learning in the classroom often experiences obstacles, primarily to teach high-level thinking skills, such as critical thinking skills. To overcome these obstacles, in this study we tried the use of peer tutors to guide their friends in a collaborative group when solving problems. This study aims to describe the impact of peer tutoring in problem-based learning on the critical thinking skills of high school physics students. This type of research is a quasi-experimental study with a pretest-posttest control group design. The sample of this research is class X MIPA 3 and X MIPA 4 SMAN 4 Jember. One class was given treatment using problem-based learning accompanied by peer tutoring, while one other class only used problem-based learning. Data about critical thinking skills were obtained from the posttest at the end of learning which was then analyzed using the Independent Sample T-test on SPSS 23. The statistical test results stated that there were differences between the average values of the experimental class and the control class. Thus, it is concluded that peer tutoring in the problem-based learning model has a significant effect on critical thinking skills. The essential aspect of thinking skills with the highest value lies in interpreting skills.